PENGARUH PEMBERIAN KOMPENSASI TERHADAP PENINGKATAN KINERJA GURU HONOR SEKOLAH DASAR (SD) DI KECAMATAN BATANG PERANAP KABUPATEN INDRAGIRI HULU - Desi Nursela; Adianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Honor teachers are non ASN teachers (State Civil Apparatus) whose welfare is not guaranteed. To realize the welfare of honorarium teachers, Batang Peranap District is inseparable from the amount of compensation provided to it. The purpose of this study was to find out, analyze and measure the effect of compensation for improving the performance of Elementary School honorarium teachers in Batang Peranap District, Indragiri Hulu Regency. This research is a quantitative study with a survey method carried out in elementary schools in Batang Peranap District. The population and sample in this study were equal to 78 respondents consisting of UPTD Education staff and Elementary School honor teachers. Data collection is done through questionnaires. After the collected data is analyzed using statistical tests through the SPSS program. The results of the study with the correlation test obtained the value of (r) count 0.754> (r) table 0.223 with a significant level of 5%. Because (r) count is greater than (r) table, it can be concluded that Ha is accepted and Ho is rejected. So there is an influence between providing compensation for improving the performance of Elementary School honorarium teachers in Batang Peranap District, Indragiri Hulu Regency. The percentage effect of variables (X) on variables (Y) is 56.9% while the remaining 43.1% is influenced by other variables. Giving compensation has a close relationship with increased performance, closeness of relations is in the range of 0.600 - 0.799 which is in the strong category.Keywords: Compensation, Performance and Honor Teachers